2019
DOI: 10.1007/s42729-019-00046-7
|View full text |Cite
|
Sign up to set email alerts
|

Fish-Scale Pits with Diversion Holes Enhance Water Conservation in Semi-arid Loess Soil: Experiments with Soil Columns, Mulching, and Simulated Rainfall

Abstract: Fish-scale pits, as one of the most important ecological engineering in semi-arid areas, especially in the Loess Plateau, China, effectively reduced water and soil loss by intercepting runoff. However, the water saved by the pits is mainly accumulated in the upper soil layer and thus easily loosed by ineffective evaporation. In this study, soil column simulation experiments were conducted to observe the effects of diversion holes on soil evaporation and soil water distribution in the loessial soil under two ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…These results emphasize that the detrimental effect of water shortage could be balanced by suitable modulation of the microclimate and contrasting the extra water losses (Losciale et al, 2011;Lopez et al, 2018;Zheng et al, 2019). Recent research suggested that deficit irrigation (75% ETc) can improve WP I with a minimal (less than 10%) reduction in yield (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 66%
“…These results emphasize that the detrimental effect of water shortage could be balanced by suitable modulation of the microclimate and contrasting the extra water losses (Losciale et al, 2011;Lopez et al, 2018;Zheng et al, 2019). Recent research suggested that deficit irrigation (75% ETc) can improve WP I with a minimal (less than 10%) reduction in yield (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 66%
“…Both gravel mulching and straw mulching can avoid direct solar radiation and reduce soil evaporation by setting physical barrier layers on the soil surface. Nevertheless, gravel mulching is the blocked channel of the water cycle between soils and the atmosphere due to gravel can block soil pores and prevent capillary water from rising (Zheng et al, 2019). That can partially explain why the gravel mulching increased soil water storage compared with straw mulching.…”
Section: Discussionmentioning
confidence: 99%
“…An Infiltration hole is a supplemental measure of slope engineering. It is vertically drilled on the ground of the installed slope engineering measures and can be fillled with a certain volume to improve infiltration (Wang et al, 2020; Zheng et al, 2019). Runoff can rapidly and directly infiltrate into the deeper soil layer via the bottom and sidewall of the hole, rather than just through the ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of increasing soil moisture and sustainable development of vegetation, planting arbors and bushes is a preferred vegetation restoration method in the semi-arid northwest of China. Certainly, some watersaving measures should be considered for vegetation restoration, such as precipitation collection with fish-scale pits and gravel mulching (Zheng et al 2019). Furthermore, soil compaction caused by machines is one common problem (Varol et al 2020), which may also affect the soil moisture status.…”
Section: The Relationship Between Soil Texture and Moisturementioning
confidence: 99%